Experimental determination of codon usage‐dependent selective pressure on high copy‐number genes in Saccharomyces cerevisiae. Issue 1 (20th January 2019) - Jossé, Lyne; Singh, Tarun; von der Haar, Tobias
Abstract: One of the central hypotheses in the theory of codon usage evolution is that in highly expressed genes, particular codon usage patterns arise because they facilitate efficient gene expression and are thus selected for in evolution. Here, we use plasmid copy number assays and growth rate measurements to explore details of the relationship between codon usage, gene expression level, and selective pressure in Saccharomyces cerevisiae . We find that when high expression levels are required, optimal codon usage is beneficial and provides a fitness advantage, consistent with evolutionary theory. However, when high expression levels are not required, optimal codon usage is surprisingly and strongly selected against. We show that this selection acts at the level of protein synthesis, and we exclude a number of molecular mechanisms as the source for this negative selective pressure including nutrient and ribosome limitations and proteotoxicity effects. These findings deepen our understanding of the evolution of codon usage bias, as well as the design of recombinant protein expression systems.